Whitman's "Song of Myself" The Structure of "Song of Myself" - Al-Nehar, Abdel Elah (Journal of Humanities & Social Sciences, 2017)
Walt Whitman’s "song of myself" is one of the original twelve pieces- first edition of Leaves of Grass appeared in. 1852. Like most of the other Whitman’s poems, "song of myself" is revised extensively till its final permutation in 1881. The song is a sprawling combination of biography, sermon, and poetic meditation. It is not nearly as heavy-handed in its pronouncements as "Starting at Paumanok", rather, Whitman uses symbols and sly commentary to get at important issues. “Song of Myself” is composed more of vignettes than lists, he uses small, precisely drawn scenes to compose his. Song of My Self does not take on the title “Song of Myself” until the 1881 edition. Previously titled “Poem of Walt Whitman, an American” and, in the 1860, 1867, and 1871 editions, simply “Walt Whitman.” The poem’s shifting title suggests Whitman’s intentions. Whitman was acquainted with the varying aspects of the metropolis, listening to the oratory of the time, becoming intimate with drivers of omnibus and ferryboat pilots, joining the crowds at bathing beaches, all of which had an effect on the manner of his poetry.  " Song of Myself" and other poems have distinctive features as repetition, parallelism, rhetorical mannerisms and the employment of the phrase instead of the foot as unit of rhythm, to create forms called free verse. "It stands to reason", says one critic, "that Whitman gave much thought to the planning and organizing of his poems" (James Miller, 1964).
Keywords: Leaves of Grass; my foot; America; Touch